Al-Quran Learning Management in the Integrated Class of Muhammadiyah 01 Junior High School Medan Kota Branch - Nasution, Ina Zainah; Hasanah, Uswah; Ulwan, Mishiyyah Nashih (Al-Ulum: Jurnal Pendidikan Islam, 2025)
The purpose of this study was to determine the planning, organization, implementation, and evaluation of Al-Quran learning in the integrated class of SMP Muhammadiyah 01. The research data instruments were observation, interview and document study. The results revealed that the integrated class of Muhammadiyah 01 Junior High School carried out the management of Al-Quran learning very well. Learning planning includes the completeness of the learning tools of subject teachers. The uniqueness of the implementation of Al-Quran learning in integrated classes can be seen from the distribution of class hours. The integrated class has six hours of Al-Quran lessons including 2 hours of Al-Quran lessons, 2 hours of Al-Quran Hadith lessons, 2 hours of Tahfiz Al-Quran lessons. Another uniqueness of Al-Quran learning management in integrated class is in the organization of learning. The organization of learning is done since the beginning of the learning year by making remedial Iqra class for students who are not fluent in reading Al-Quran and Tahfiz class. The implementation or application in learning every teacher is able to manage the class well, so that the teaching and learning process can run optimally. Evaluation is also carried out daily, monthly, midterm, and semester. The evaluation of learning in the integrated class is carried out in various ways, namely oral, written, and demonstration of reading skills.